Epigenome-wide association study reveals duration of breastfeeding is associated with epigenetic differences in children - Sherwood, William B.; Kothalawala, Dilini M.; Kadalayil, Latha; Ewart, Susan; Zhang, Hongmei; Karmaus, Wilfried; Arshad, Syed Hasan; Holloway, John W.; Rezwan, Faisal I. (MDPI, 2020)
Several small studies have shown associations between breastfeeding and genome-wide DNA methylation (DNAm). We performed a comprehensive Epigenome-Wide Association Study (EWAS) to identify associations between breastfeeding and DNAm patterns in childhood. We analysed DNAm data from the Isle of Wight Birth Cohort at birth, 10, 18 and 26 years. The feeding method was categorized as breastfeeding duration >3 months and >6 months, and exclusive breastfeeding duration >3 months. EWASs using robust linear regression were performed to identify differentially methylated positions (DMPs) in breastfed and non-breastfed children at age 10 (false discovery rate of 5%). Differentially methylated regions (DMRs) were identified using comb-p. The persistence of significant associations was evaluated in neonates and individuals at 18 and 26 years. Two DMPs, in genes SNX25 and LINC00840, were significantly associated with breastfeeding duration >6 months at 10 years and was replicated for >3 months of exclusive breastfeeding. Additionally, a significant DMR spanning the gene FDFT1 was identified in 10-year-old children who were exposed to a breastfeeding duration >3 months. None of these signals persisted to 18 or 26 years. This study lends further support for a suggestive role of DNAm in the known benefits of breastfeeding on a child’s future health
Keywords: epigenetics; breastfeeding duration; breastfeeding; Epigenome-Wide Association Study; EWAS; DNA methylation